The Role of Epicardial Adipose Tissue in the Development of Atrial Fibrillation, Coronary Artery Disease and Chronic Heart Failure in the Context of Obesity and Type 2 Diabetes Mellitus: A Narrative Review - Anirudh Krishnan; Harman Sharma; Daniel Yuan; Alexandra F. Trollope; Lisa Chilton (Journal of Cardiovascular Development and Disease, 2022)
Cardiovascular diseases (CVDs) are a significant burden globally and are especially prevalent in obese and/or diabetic populations. Epicardial adipose tissue (EAT) surrounding the heart has been implicated in the development of CVDs as EAT can shift from a protective to a maladaptive phenotype in diseased states. In diabetic and obese patients, an elevated EAT mass both secretes pro-fibrotic/pro-inflammatory adipokines and forms intramyocardial fibrofatty infiltrates. This narrative review considers the proposed pathophysiological roles of EAT in CVDs. Diabetes is associated with a disordered energy utilization in the heart, which promotes intramyocardial fat and structural remodeling. Fibrofatty infiltrates are associated with abnormal cardiomyocyte calcium handling and repolarization, increasing the probability of afterdepolarizations. The inflammatory phenotype also promotes lateralization of connexin (Cx) proteins, undermining unidirectional conduction. These changes are associated with conduction heterogeneity, together creating a substrate for atrial fibrillation (AF). EAT is also strongly implicated in coronary artery disease (CAD); inflammatory adipokines from peri-vascular fat can modulate intra-luminal homeostasis through an “outside-to-inside” mechanism. EAT is also a significant source of sympathetic neurotransmitters, which promote progressive diastolic dysfunction with eventual cardiac failure. Further investigations on the behavior of EAT in diabetic/obese patients with CVD could help elucidate the pathogenesis and uncover potential therapeutic targets.